2010
DOI: 10.1261/rna.2232710
|View full text |Cite
|
Sign up to set email alerts
|

Functional elucidation of a key contact between tRNA and the large ribosomal subunit rRNA during decoding

Abstract: The selection of cognate tRNAs during translation is specified by a kinetic discrimination mechanism driven by distinct structural states of the ribosome. While the biochemical steps that drive the tRNA selection process have been carefully documented, it remains unclear how recognition of matched codon:anticodon helices in the small subunit facilitate global rearrangements in the ribosome complex that efficiently promote tRNA decoding. Here we use an in vitro selection approach to isolate tRNA Trp miscoding v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…In our previous work, we found that tRNA Trp -miscoding tRNAs exploit an interaction with residue A1913 of H69 to effectively accommodate on certain near-cognate codon ribosome complexes (21). These results are extended in Fig.…”
Section: Transient Kinetic Analysis Of Effects Of H69 Mutations On Sesupporting
confidence: 65%
See 3 more Smart Citations
“…In our previous work, we found that tRNA Trp -miscoding tRNAs exploit an interaction with residue A1913 of H69 to effectively accommodate on certain near-cognate codon ribosome complexes (21). These results are extended in Fig.…”
Section: Transient Kinetic Analysis Of Effects Of H69 Mutations On Sesupporting
confidence: 65%
“…Although there are numerous examples in the literature where both GTPase activation and accommodation are similarly affected by a miscoding tRNA (11,12), we have recently shown that a mutation in the elbow region of tRNA Trp-G59A stimulates accommodation, but not GTPase activation, on a near-cognate codon (21). Interestingly, this variant tRNA also depends on H69 residue A1913 to stimulate this accommodation step.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…8 H69 contains three modified nucleotides, two pseudouridines (Ψ) 7b and one 3-methylpseudouridine (m 3 Ψ) 7a (Figure 2), which are important for ribosome function 8a, 8b, 9 and modulation of the loop structure. 9c, 9d, 10 H69 has also been implicated in a number of key ribosome functions such as ribosome recycling, 11 tRNA selection, 12 translational fidelity, 13 and subunit association, 8a, 9a making it an attractive target for antibiotic drug design.…”
Section: Introductionmentioning
confidence: 99%